2013
DOI: 10.1111/tid.12170
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nontuberculous mycobacterial infections in solid organ transplant recipients: a case–control study

Abstract: Additional studies are needed to evaluate the role of targeted surveillance measures for NTM disease in high-risk patients, particularly lung transplant recipients, and to characterize the mechanisms of disease acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 13 publications
2
61
1
1
Order By: Relevance
“…Redelman-Sidi et al reported 44 cases of M. abscessus complex over a 10-year period at a large cancer center in New York [22]; Candido et al reported 30/129 patients with cystic fibrosis with NTM pulmonary infections over a 4-year period in Brazil [23]. Longworth et al recently reported 15 cases of M. abscessus out of 34 (44%) NTB infections in solid organ transplant recipients over a 7.5-year period [24], and Knoll et al reported 5/53 (9.4%) cases of M. abscessus complex in 53 transplant recipient patients who had 1 or more cultures positive for NTM over 15 years [25]. Smaller cases series of M. abscessus complex have been reported by others [26–28].…”
Section: Discussionmentioning
confidence: 99%
“…Redelman-Sidi et al reported 44 cases of M. abscessus complex over a 10-year period at a large cancer center in New York [22]; Candido et al reported 30/129 patients with cystic fibrosis with NTM pulmonary infections over a 4-year period in Brazil [23]. Longworth et al recently reported 15 cases of M. abscessus out of 34 (44%) NTB infections in solid organ transplant recipients over a 7.5-year period [24], and Knoll et al reported 5/53 (9.4%) cases of M. abscessus complex in 53 transplant recipient patients who had 1 or more cultures positive for NTM over 15 years [25]. Smaller cases series of M. abscessus complex have been reported by others [26–28].…”
Section: Discussionmentioning
confidence: 99%
“…When present, they most commonly manifest as pulmonary and multifocal cutaneous infections. 57 Treatment of tuberculosis in this population has its own concerns. Rifampicin is a strong enzyme inducer and may increase metabolism of cytochrome P-450 significantly.…”
Section: Correct Answers: a And Cmentioning
confidence: 99%
“…Mycobacterium abscessus and Mycobacterium avium complex were the most common pathogens, and the lung (including pleura) was the most common site of disease. In this adjusted case-control analysis, lung transplant recipients had the highest risk of NTM disease [52]. According to Knoll et al, NTM were isolated from 53 of 237 patients (22.4%) following lung transplantation over a median of 25.2 months follow-up.…”
Section: Ntm and Organ Transplantationmentioning
confidence: 99%